Gödelisation in the lambda-Calculus - Goldberg, Mayer (BRICS Report Series, 1995)
Gödelisation is a meta-linguistic encoding of terms in a language. While it is impossible to define an operator in the lambda-calculus which encodes all closed lambda-expressions, it is possible to construct restricted versions of such an encoding operator. In this paper, we propose such an encoding operator for proper combinators. See also BRICS RS-96-5